Implementation of "E-Lens" inquiry-based learning game to improve literacy and numeracy skills - Rahayu, Widya Adhariyanty; Subekti, Puji (Jurnal Cakrawala Pendidikan, 2025)
Literacy and numeracy are two fundamental skills that play a crucial role in the elementary education process. Literacy encompasses not only reading and writing skills but also the ability to understand information effectively. Meanwhile, numeracy includes the ability to understand and interpret mathematical concepts in everyday life. This research used the ADDIE model to develop a learning media in the form of E-Lens board game, namely Exploring Literacy, Numeracy, Math, and English. This research was conducted at Taji State Elementary School, located in a rural area, in the easternmost village on the slopes of Mount Bromo. In terms of infrastructure, the school has limited accessibility, especially regarding internet and conventional learning resources. The learning media was validated by media and material experts. Media expert assessment obtained an average percentage of 79.2% and the material expert has an average percentage of 77%. The validation results indicated that E-Lens board game, which is based on bilingual inquiry, are very good to be used as a learning media for developing numeracy literacy at the elementary level. Based on research stages and feedback from media, material experts, and respondents, E-Lens as learning media can improve elementary students’ literacy and numeracy skills.